KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS XI SMA NEGERI 14 PADANG - Sapitri, Yohana; Abdurrahman, Abdurrahman (Universitas Negeri Padang, 2019)
ABSTRACT This article reveals the correlation of reading comprehension skills with writing skills of explanatory texts grade students XI SMA Negeri Padang 14. There are three purposes of this study. First, to describe the reading comprehension skills of class XI SMA Negeri 14 Padang. Second, to describe the explanatory text writing skills of class XI SMA Negeri 14 Padang . Third, to describe the correlation of reading comprehension skills with explanatory text writing skills in class XI SMA Negeri 14 Padang. This type of research is quantitative with descriptive method. The design used in this study is correlation design. The population of this study is was XI SMA Negeri 14 who were enrolled in the 2018/2019 school year, which was 273 students. The sample in this study was determined by proportional random sampling of 15% of the population which is 40 students. The research data is in the form of scores on the result of explanatory writing skills. The istrument of this study is an objective test to measure comprehension reading skills and performance tests to measure explanatory writing skills. The results of this study are three. First, the reading comprehension skills of students XI SMA Negeri 14 Padang are in good qualification (B). Second, explanatory text writing skills of students XI SMA Negeri 14 Padang are in good qualification (B). Third, reading comprehension skills have a significant correlation with explanatory text writing skills of the eleventh grade students XI SMA Negeri 14 Padang of at 76%, while remaining 24% is influenced by other factors not examined in this study. Kata kunci: Korelasi, Keterampilan, Membaca Pemahaman, Menulis, Teks Eksplanasi